Placenta praevia in U.S.M.: A review - Hanafiah, Zainal Abidin Hj (1995)
The Obstetrics and Gynaecological case records of 190 patients with proven placenta praevia have been reviewed between January 1990 till December 1992 . With equal number of controls both groups were compared for predisposing factors namely previous caesarean sections and previous abortions. The outcome between symptomatic (n=148) and asymptomatic (n=42) group were looked into with regards to maternal and perinatal morbidity, maternal age group, parity, gestational age at diagnosis, gestational age at delivery, birthweight, duration of admission, the need of blood of transfusions and mode of delivery. There was significant relation between placenta praevia and previous caesarean section ( p< 0.05 ), and previous abortions ( p< 0.05 ). Those patients without bleeding delivered a significantly larger baby and spent less time in the hospital. They also were found to have a significantly lower rate of emergency caesarean section. The occurrence of bleeding was significantly more in those with central placenta praevia (type 4 ) than other types.